Molecular characterization of Cryptosporidium spp. in sheep and goat in Al-Qadisiyah province/ Iraq: Mansoor Jadaan Ali Alkhaled and Weam Abbas Hamad - Alkhaled, Mansoor Jadaan Ali (The Iraqi Journal of Veterinary Medicine, 2018)
The present study was conducted during the period from September 2015 until February 2016. 100 fecal samples were collected from 60 sheep and 40 goats for diagnosis of Cryptosporidium parasite from diverse areas in Al-Qadisiyah province. The study amid to know the genetic characters of Cryptosporidium spp. parasite by using a molecular technique such as the nested polymerase chain reaction and DNA sequencing analyzed by phylogenetic tree to identify the parasite species. This study was done on the sheep and goat at first time in the middle region of Iraq and the identified species were recorded in NCBI-Genbank database. In sheep, the results of positive infected samples was (40%) while, in the goats were (32.5%), the DNA sequencing and phylogenetic analysis method based on small ribosomal RNA gene (18s rRNA) for Cryptosporidium species typing. The results were conducted by Neighbor-Joining phylogenetic tree analysis method and the 18s rRNA gene sequences were confirmed by using NCBI-BLAST data analysis in order to compare with NCBI submitted selected references isolates of (18s ribosomal RNA) gene in Cryptosporidium spp. parasites. Our finding in present study appeared to follow spp. (C. parvum, C. hominis, C. andersoni, C. ubiquitum, C. xiaio and C. suis). These identified species which primary affected sheep and goats as mentioned in previous studies when compared with newly Iraq isolates strains.